Suspicious object detection - Joshi, Tarushikha; Aarya, Harsh; Kumar, Prashant (2016 2nd International Conference on Advances in Computing, Communication, & Automation (ICACCA) (Fall), 2016)
This paper presents a method for automatic detection of a suspicious object in public places (like railway station, airports, bus stand etc). The suspicious object will be carried by a person in the scene. An object area is extracted using background subtraction. For selecting an object of interest a unique label has been assigned to all the objects. For labeling of objects, connected component labeling algorithm has been used. A suspicious object is any object that is unattended for a specific time period. An object can be declared as suspicious on the basis of the distance of the object from its owner for a specific time period. We are using Matlab to develop this system.